2006
DOI: 10.1086/507426
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Dynamics and Prospective Environmental Sampling of Adenovirus in a Military Recruit Setting

Abstract: Potential sources of adenovirus transmission among US military recruits included the presence of adenovirus on surfaces in living quarters and extended pharyngeal viral shedding over the course of several days. The introduction of new recruits, who were still shedding adenovirus, into new training groups was documented. Serological screening could identify susceptible recruits for the optimal use of available vaccines. New high-throughput technologies show promise in providing valuable data for clinical and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
91
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 28 publications
(27 reference statements)
2
91
0
Order By: Relevance
“…In addition, according to a former study, rifles were most commonly observed in the military environment. Therefore, FT may be a risk factor for the spread of adenovirus and a cause of FRI in the army (23). However, further studies are required to clarify these associations (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, according to a former study, rifles were most commonly observed in the military environment. Therefore, FT may be a risk factor for the spread of adenovirus and a cause of FRI in the army (23). However, further studies are required to clarify these associations (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The epidemiological investigation was conducted by 3 military doctors, namely 2 preventive medicine specialists and 1 infectious medicine specialist of the Armed Forces Medical Command, from March 22 to 23,2012. During the epidemiological investigation, we surveyed symptoms and identified 161 FRI cases and index cases by case definition and onset days, analyzed the association between different types of military training courses with the onset of FRI, and estimated the attack rate among 161 patients with FRI and pneumonia.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with the general population, our population is known to be highly immune to Ad-4 and to have a relatively high degree of immunity to Ad-7. 22 However, although theoretically possible, Ad-4…”
mentioning
confidence: 99%
“…Ad4 and Ad7, for example, cross-react despite their being from different species. 22 Nevertheless, there is no evidence that these cross-react with Ad-36. One possible limitation to the study's conduct was the misidentification of obese subjects.…”
mentioning
confidence: 99%
“…Further, outbreaks of shigellosis (6), cryptosporidiosis (7), and giardiasis (8,9) indicate that other highly infectious enteric pathogens can spread from person to person after being introduced into a community through water, food, or other sources (9). Recent adenovirus outbreak data indicate that persons with asymptomatic infection who are shedding virus can be a primary cause of continual transmission of infection (10). And in a prolonged giardiasis outbreak that occurred in late 2003 in a Boston, Massachusetts, suburb, 30 primary cases of giardiasis attributed to a children's swimming pool resulted in 105 secondary cases among persons from the same or socially related households.…”
mentioning
confidence: 99%